The analysis of vibration characteristics of rotor system with delay effects - Zhang, Yue; Xue, Zhihui; Yang, Yuejuan; Yu, Yangyang; Pang, Guoying (Sound & Vibration, 2026)
The rotor system, as the core component of rotating machinery, its dynamic characteristics directly affect the safe and stable operation of the equipment. The seal components ensure the sealing performance of the system, but the unsteady flow of gas in the sealing gap will induce delay-type nonlinear seal forces and affect the vibration characteristics. This paper studies the vibration characteristics of rotor systems with delay effects. Firstly, the complexity of the sealing structure causes air flow disturbances, resulting in displacement delay feedback excitation. Therefore, the rotor system dynamic model containing displacement delay feedback is established. Secondly, the stability operating boundaries are derived based on the eigenvalue analysis method, revealing the influence mechanism of delay parameters on the steady-state operation. It is obtained that the stability boundary undergoes periodic migration under the combined effect of delay and feedback intensity. Finally, the accuracy of the proposed model is verified through numerical simulation. The research shows that time delay induces nonlinear vibration characteristics. At a rotational speed of 1,000 rad/s, the time delay exceeding 0.24 s drives the system into a chaotic operating state, which is detrimental to stable operation. Furthermore, the value of the seal parameter  significantly affects the operating state of the rotor system. This work provides a theoretical basis for the dynamic modeling, stability analysis, and vibration control of rotor systems with delay effects, and has engineering significance for the reliable operation of high-speed rotating machinery.